Antecedents, mediation effects and outcomes of hotel eco-innovation practice. (February 2020) - Wang, Yajun; Font, Xavier; Liu, Jingyan
Highlights: Hotels' eco-innovations are the results of dynamic capabilities, top managers' attitudes and stakeholder pressures. Opportunity-capitalizing capability has more weight than the other three antecedents. Differentiation advantage is a short-term path from eco-innovation to improved performance. Cost competitive advantage might be a long-term path from eco-innovation to improved performance. Eco-innovation is the key mediator between the antecedents and competitive advantages. Abstract: Eco-innovation is essential if we are to improve the environmental impacts of tourism firms. Building on the natural-resource-based view (NRBV) of the firm, we hypothesize that eco-innovation is the mediating factor between four firm-level antecedents ( opportunity-recognizing and opportunity-capitalizing capabilities, top managers' attitudes and stakeholder pressures ) and three outcomes ( cost and differentiation, with respect to a firm's competitive advantage, and its resulting organizational performance ). Partial least squares structural equation modelling is applied to the data from a survey with hotel managers in China, and confirms all of the hypotheses, except two, namely: i) that cost competitive advantage is positively related to hotel performance, and ii) that eco-innovation fully mediates the relationships between opportunity-recognizing capability and both dimensions of competitive advantage. Our contribution to the NRBV theory with a novel, integrated model to predict the mediating role that eco-innovation plays between firm-level resources and capabilities, and competitive advantages.